Macroscopic versus microscopic photovoltaic response of heterojunctions based on mechanochemically prepared nanopowders of kesterite and n-type semiconductors - Dimitriev, O.P.; Grynko, D.O.; Fedoryak, A.M.; Doroshenko, T.P.; Kratzer, M.; Teichert, C.; Noskov, Yu.V.; Ogurtsov, N.A.; Pud, A.A.; Balaz, P.; Balaz, M.; Tesinsky, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
Mechanochemically prepared nanopowder of selenium-free kesterite Cu₂ZnSnS₄ (CZTS) in combination with n-type semiconductors, i.e., CdS, ZnO, and TiO₂, was tested in planar and bulk-heterojunction solar cells. The samples have been studied by macroscopic current-voltage (I-V) measurements and Kelvin-probe atomic force microscopy (KPFM). KPFM images taken under light illumination showed the distribution of the potential across the surface, with negative potential on the n-type semiconductor domains and positive potential on the CZTS domains, which indicated charge separation at the interface of the counterparts. The best result was found for the CdS-CZTS composition, which showed a potential difference between the domains up to 250 mV. These results were compared with planar heterojunctions of CdS/CZTS and TiO₂/CZTS, in which CZTS nanopowder was pressed/deposited directly onto the surfaces of films of the corresponding n-type semiconductors. Again, I-V characteristics showed that cells based on CdS/CZTS heterojunctions have the best performance, with a photovoltage up to 200 mV and photocurrent densities up to 0.1 mA/cm². However, the carrier generation was found to occur mainly in the CdS semiconductor, while CZTS showed no photo-response and served as the hole-transporting layer only. It is concluded that sensitization of the kesterite powder obtained by the mechanochemical method is necessary to improve the performance of the corresponding solar cells.